Audiovestibular manifestations during pregnancy: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2022)
Pregnancy is nine-month duration physiological process with psychological, cardiovascular, and hormonal changes that affects different organs of the pregnant women. Any organs of the body can be affected during pregnancy due to hormonal changes so as in audiovestibular system. There are several audiovestibular manifestations occur during pregnancy such as hearing loss, otosclerosis, tinnitus, autophony, facial nerve palsy, and vertigo manifested as first time or get exacerbated during pregnancy. Majority of the changes during pregnancy are harmless to the mother and fetus, whereas some may cause pathological manifestations. The hormonal changes during pregnancy can cause alteration in the homeostasis of the inner ear fluids and hamper the inner ear functions. The changes of estrogen and progesterone levels during pregnancy can affect the audio-vestibular system. These changes in the inner ear may manifest with symptoms like vertigo, tinnitus, fullness in the ear, and hyperacusis. These symptoms in the pregnancy directly affects the quality of life both physically and emotionally. There are no standard guidelines for the management of audiovestibular manifestations. However, there are very little data available for audiovestibular manifestations during the pregnancy period. The objective of this review article is to discuss the prevalence, etiopathology, and clinical presentations, diagnosis and treatment of audiovestibular manifestations during pregnancy.